An efficient numerical solution of time--fractional batch reactor system - Alwahhah, Saad Yusur (IJRDO -JOURNAL OF MATHEMATICS, 2019)
Recently, an approximate solution of the time fractional chemical engineering equations by means of the homotopy perturbation method (HPM) has been presented by Khan et al. \cite{khan2010approximate}. As a disadvantage of the HPM, to have reasonable solution at large values of $t$ we should truncate \text{HPM} series with more terms, while this task is so complicated and even takes too time to complete. In this paper, we have successively applied the predictor--corrector approach on fractional chemical systems to obtain an accurate numerical solution. The numerical results are compared with obtained results by HPM. This comparison shows that predictor--corrector approach is more accurate than the HPM. As advantages of predictor-corrector over the HPM, the method reduces the computational difficulties and is easy to implement.